Ultrasound Imaging in Settings of a Natural Disaster: Experience from October 8th 2015 Earthquake in Pakistan - Ahmad, Fayyaz; Mahmood, Tariq; Memon, Abdul Shakoor; Jamali, A.R.; Abbas, Kausar (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
Ultrasound (U/S) imaging has a broad spectrum of applications in medical practice. The earthquake of October 8, 2005 was one of the most severe in the history of Pakistan, claiming around 80,000 lives in the region of Azad Kashmir. U/S imaging was the only diagnostic radiological investigation available in the region. The study was aimed to evaluate the role of U/S in diagnosing internal injuries among victims of the earthquake. All the patients referred for U/S imaging at Abbas Institute of Medical Sciences (AIMS) were accordingly examined and the data was recorded on a proforma. The procedures included examination of chest, abdomen, pelvis, extremities and fetal wellbeing (FWB). U/S findings were correlated with clinical, laboratory or surgical exploratory findings. A total of 87 patients, 22 males and 65 females, were examined. Definitive diagnoses were established in 16.8% of abdominal examination cases, 76.6% of abdomen/pelvis examinations and 78.6% of Gynae & Obstetric examination cases. The course of management was changed completely using U/S observations in 36% of the cases of chest examinations, 71.9% of the cases of abdominal & pelvic examination and 75.8% of the cases of Gynae & Obstetrics. It was concluded that U/S is a useful diagnostic modality in the settings of a natural disaster. Head and spine injuries, however, cannot be assessed with this diagnostic modality and needs special consideration.